Calcium Electrochemotherapy and Challenges in Combined Treatment with Dendritic Cell Vaccination - Eivina Radzevičiūtė-Valčiukė; Austėja Balevičiūtė; Augustinas Želvys; Karolina Suveizdė; Auksė Zinkevičienė; Vytautas Kašėta; Veronika Malyško-Ptašinskė; Neringa Dobrovolskienė; Vita Pašukonienė; Jurij Novickij; Irutė Girkontaitė; Vitalij Novickij (Pharmaceutics)
Background/Objectives: Electrochemotherapy (ECT) is a reliable and potent technique for managing primary tumors; however, significant efforts are being made to characterize and improve the systemic immune response, which is crucial for metastasis prevention. Current evidence suggests that the advancement of ECT will depend on its integration with complementary immunomodulatory methods. Methods: In this study, we examined the combined effects of calcium-based electrochemotherapy (CaECT, 1.3 kV/cm × 100 µs, eight pulses delivered at 1 Hz repetition frequency) with dendritic cell vaccination (DCV). Lewis lung carcinoma (LLC1) was used as a tumor model. We characterized the effects of CaECT alone and in combination with DCV therapy on tumor growth, analyzed the changes in immune cell subpopulations, and studied the humoral immune response dynamics on day 10, 20, and 30. Given the limited effect of DCV, additional experiments were conducted with the chemotherapeutic drug cyclophosphamide (CP), known for its immunomodulatory properties. Results: Although CaECT demonstrated potent antitumor activity and induced a significant immune response, its combination with DCV did not result in enhanced therapeutic efficacy. The combination of CP also failed to improve median survival. Conclusions: It is concluded that CaECT is a promising alternative to standard ECT involving bleomycin or cisplatin. However, further optimization is necessary to enhance the therapeutic synergy of CaECT when combined with DCV.